1995
DOI: 10.1111/j.1439-0450.1995.tb00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Naturally Occurring Zeranol in Bovine Bile in Northern Ireland

Abstract: Summary Zeranol and two Fusarium toxins, α‐zearalenol and ß‐zearalenol, were confirmed by gaschromatography/mass spectrometry (GC/MS) in bovine bile samples referred to this laboratory for analysis. No evidence of zeranol abuse was found on‐farm. Given the recent suggestion that zeranol might arise from the metabolism of these Fusarium toxins, and the finding of zeranol in bovine and ovine urine across the EU, it was concluded that the residues had arisen as a result of natural metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
1
12
0
1
Order By: Relevance
“…The authors suggest that the formation of α-ZAL may occur primarily via reduction of α-ZOL, probably in the reductive environment of the rumen. The results are in agreement with earlier investigations which implied that α-ZAL can occur in domestic animals without deliberate α-ZAL treatment (Erasmuson et al, 1994;Kennedy et al, 1995;Miles et al, 1996; Figure 2). Moreover, Kennedy et al (1998) found significantly higher α-ZOL (12-fold) and β-ZOL (9-fold) concentrations in the α-ZAL positive samples than in the α-ZAL negative samples with an α-ZAL: α-ZOL ratio of at least 1:5.…”
Section: Deoxynivalenolsupporting
confidence: 93%
“…The authors suggest that the formation of α-ZAL may occur primarily via reduction of α-ZOL, probably in the reductive environment of the rumen. The results are in agreement with earlier investigations which implied that α-ZAL can occur in domestic animals without deliberate α-ZAL treatment (Erasmuson et al, 1994;Kennedy et al, 1995;Miles et al, 1996; Figure 2). Moreover, Kennedy et al (1998) found significantly higher α-ZOL (12-fold) and β-ZOL (9-fold) concentrations in the α-ZAL positive samples than in the α-ZAL negative samples with an α-ZAL: α-ZOL ratio of at least 1:5.…”
Section: Deoxynivalenolsupporting
confidence: 93%
“…a-ZEL and b-ZEL are also metabolites of ZEN formed in various animal species and in humans [2,[6][7][8]. In ruminants, the formation of small amounts of a-ZAL and b-ZAL has been demonstrated [9,10]. a-ZAL is also called zeranol and used in the USA and Canada, but not in the EU, as a growth promotor in cattle under the trade name RalGro s [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different metabolites of zearalenone, the non-steroidal oestrogenic ␣-zearalanol (zeranol) has been marketed as a growth promoter [135][136][137] with estrogenic activity with the commercial name "Ralgro". Thus, the finding of zeranol in an animal might, on its own, be an in sufficient proof that malicious abuse of zeranol has occurred.…”
Section: Detection Of Hormones With a Hemi-endogenous Statusmentioning
confidence: 99%